Assessing the Immobilization of Heavy Metals in Compost Derived from Organic Fraction of Municipal Solid Waste Amended with Forest-based Biochar - Omid Hassanzadeh Moghimi; Ali Daryabeigi Zand; Gholamreza Nabi Bidhendi (Environmental Energy and Economic Research, 2022)
Biochar is characterized by a large specific surface area, porosity, and a large number of functional groups. All of those features causes that biochar can be a potentially good material in the optimization of the process of composting and final compost quality. The aim of this study was to assess the effect of biochar to reduce the bio-availability of heavy metals (HMs) during the composting of organic fraction of municipal solid waste (OFMSW) and to improve the end product quality. Small selected doses of biochar (1%, 3%, and 5% by weight of the OFMSW) were added to the compost piles, and compared with a control without any amendment. The results indicated that the biochar effectively reduced the bio-availability of HMs (Pb, Zn, Ni, Cd, and Cu) compared to control. The combine use of OFMSW + 5% biochar was significantly reduced the Cd content by 71.63% as compare to control. Also, biochar addition at 1% and 3% could reduce the Cd content in final product of the compost respectively by 55.82% and 70.24%. The addition of biochar (even low doses of 1%), lowered the concentrations of HMs to those recommended by compost quality standards. Therefore, the application of biochar as a beneficial additive can improve the quality of compost produced from the OFMSW and provide good conditions for the use of the produced compost as an enhancer of agricultural soil.